BURDEN OF THE PAST: POSTCOLONIAL SILENCE AND INTERGENERATIONAL TRAUMA IN ABDULRAZAK GURNAH’S AFTERLIVES (Al-Aasar, 2025)
This paper examines the role of postcolonial silence in shaping intergenerational trauma in Abdulrazak Gurnah’s Afterlives through Judith Lewis Herman’s trauma theory. It explores how historical violence and the colonial legacies of Germany and Britain shape the social and psychological realities of characters such as Khalifa, Ilyas, Hamza and Afiya across generations. Through diverse characterizations, Gurnah highlights distinct types of silence – strategic, traumatic, and redemptive – while also tracing the characters' journeys toward healing from postcolonial trauma. The study argues that colonial legacies, alongside personal and historical trauma, disrupt the lives of the characters, guiding them to navigate and reshape their fractured identities. Drawing on Herman’s trauma recovery model, this research examines how characters struggle and expatriates process their traumatic experiences, providing a space for identity reconstruction. Using a qualitative approach, the study closely analyzes patterns of silence, historical trauma, and inherited memory. The findings reveal that silence in Afterlives is not merely an absence but an active force that sustains intergenerational trauma while simultaneously offering pathways to resistance and healing. Ultimately, the paper highlights the enduring weight of historical trauma and how the past continues to shape individual and collective identities in postcolonial contexts, with silence remaining central to these negotiations.